Deteksi Penyakit Zoonosis Ehrlichiosis pada Pasien Anjing di Klinik Hewan Jogja - Dela Ria Nesti; Ahmad Baidlowi; Febri Ariyanti; Ida Tjahajati (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Ehrlichiosis is a zoonotic diseases caused by blood parasitic infection that can be transmitted by a ticks. Dogs infected with Ehrlichiosis canis who not treated for long periods of time can cause anemia and result in death. Although many diseases are found in the field but the percentage rate of the incidence of the disease is unknown. This study aims to detect Ehrlichiosis disease in dog patients treated at Jogja Veteinary Clinic by using Ehrlichiosis diagnosis kit available in the field. The material used in this study used dog patients who came to the Jogja Veterinary Clinic during April to September 2017. Dog patients who showed signs of infection of blood parasites with clinical symptoms of appetite and drinking down, weak, lethargic, found the presence of a ticks, or there history of infected ticks was included in the study. Patients who entered the study criteria, then taken the blood through the vena cephalika by using a 3 ml sterile syringe. Furthermore, fresh blood drops on the Ehrlichiosis detection kit according to the manufacturer's instructions. Furthermore, the results are positive if found two lines and negative when only seen one line. Data of research result are presented in tabular form and percentage of disease according to result obtained. The results of the research showed that there were 7,63% (15/1,785) positive dogs suffering from Ehrlichiosis. These results can illustrate the incidence of Ehrlichiosis in dogs, especially in dog patients treated at the Jogja Veterinary Clinic, because of the danger of Ehrlichiosis (zoonotic), awarness is needed.